The microplastics occurrence and toxic effects in marine environment - Yap, How Swen; Shukor, Mohd Yunus; Yasid, Nur Adeela (Hibiscus Publisher, 2022)
The ubiquitous plastic contaminant is impossible to avoid in today's world and occurs in the marine environment as microplastic particles, which are particles larger than 5 millimeters. It has been discovered that there is pollution in the ocean caused by plastics in areas that were previously thought to be pristine. These areas include the oceans of the Arctic and Antarctic. Many marine ecosystems are negatively impacted by plastic pollution caused by a variety of human activities, which can occur via a variety of pathways. In light of this, the purpose of this review is to talk about marine microplastics while putting an emphasis on the possible occurrence routes taken into marine ecosystems with subsequent sedimentation events. Recent research has pointed to the possibility of using plastic bioremediation as a method for its removal; consequently, this mini review covers the potential exploitation of marine microorganisms and animals has been analyzed in light of the problem of marine plastic pollution.